2020
DOI: 10.1126/science.aax4079
|View full text |Cite
|
Sign up to set email alerts
|

The pan-genome effector-triggered immunity landscape of a host-pathogen interaction

Abstract: Effector-triggered immunity (ETI), induced by host immune receptors in response to microbial effectors, protects plants against virulent pathogens. However, a systematic study of ETI prevalence against species-wide pathogen diversity is lacking. We constructed the Pseudomonas syringae Type III Effector Compendium (PsyTEC) to reduce the pan-genome complexity of 5127 unique effector proteins, distributed among 70 families from 494 strains, to 529 representative alleles. We screened PsyTEC on the model plant Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
239
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(252 citation statements)
references
References 68 publications
11
239
1
1
Order By: Relevance
“…These could be mediated, at least partially, by specific T3Es that promote virulence and/or suppress plant basal defences. T3Es are known determinants of host specificity of plant‐pathogenic bacteria (Alfano, 2009; Laflamme et al ., 2020). It is well known that Group I and II strains differ in their T3E arsenal (Eckshtain‐Levi et al ., 2014; Jiménez‐Guerrero et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These could be mediated, at least partially, by specific T3Es that promote virulence and/or suppress plant basal defences. T3Es are known determinants of host specificity of plant‐pathogenic bacteria (Alfano, 2009; Laflamme et al ., 2020). It is well known that Group I and II strains differ in their T3E arsenal (Eckshtain‐Levi et al ., 2014; Jiménez‐Guerrero et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…ETI is mediated by plant nucleotide-binding, leucine-rich repeat (NLR) proteins, which either directly or indirectly detect the activities of specific T3SEs (Jones and Dangl, 2006;Khan et al, 2016). These ETI responses can be associated with a hypersensitive cell death response (HR), which is associated with greater reductions in pathogen growth (Laflamme et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic investigation of the ETI landscape of the Pseudomonas syringae -Arabidopsis thaliana (hereafter Arabidopsis) model pathosystem revealed that ETI is a pervasive form of immunity, where nearly all P. syringae strains carry at least one T3SE capable of eliciting ETI (Laflamme et al, 2020). This near complete immunity against P. syringae can be conferred by a small number of NLR proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Although we cannot rule out an additional role for miR825-5p in regulating ETI, since miR825-5p targeted genes encode uncharacterized TNLs, it would have to be on the regulation of ETI mediated by a yet uncharacterized effector/R-gene pair in the Arabidopsis / P. syringae pathosystem or by effectors from a different bacterial or fungal pathogen. On this note, AT5G18360, a putative primary target for miR825-5p, has been recently identified as a TNL involved in triggering ETI against Pto DC3000 effector HopB [79]. As proposed in tomato [35], miR825-5p may have a quantitative contribution to plant defenses, perhaps controlling low-level recognition of pathogen effectors in the absence of proper ETI.…”
Section: Discussionmentioning
confidence: 99%